2(n - 1) + 4n = 2(3n - 1)
2n - 2 + 4n = 6n -2
6n - 2 = 6n - 2 (equal)
6n - 6n = 2 - 2
0 = 0
whatever value you put into the place of n, you'll get 0 = 0
Hey there!
Okay, so when you get a problem like this, all you need to do in insert the given value into the function and solve.
For example:
As you can see, they state that <em>(a) = 27, </em>so you insert 27 in for a in the function and it will look like this:
h(27) = 3(27) + 5
Now you solve on the right side of the equal sign:
3(27) = 81 (you multiply them)
81 + 5 = 86
When you plug the value of 27 in for a in this function, your output is equal to 86.
Răspunsul corect va fi numărul 4. Supãrat dacã meu vorbind nu este cel mai bun, vorbesc limba engleza. Dacă ai nevoie de numere consecutive, sunt 99, 102 şi 103.
C
14²+21²-√49
196+441-7
630
Mark brainliest please